PENGARUH HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN LIPSTIK HANASUI DI ARABELLE TDM 2 KOTA KUPANG - Yuliana Sarlince Malo; David R.E Selan; Kretisana Jagi (Jurnal Administrasi Terapan, 2025)
This study aims to determine the influence of price and brand on Hanasui lipstick purchasing decisions at Arabelle TDM 2 in Kupang City. The research uses a quantitative approach with an associative research design. The sample consists of 100 respondents selected through purposive sampling, meeting the criteria of consumers who have purchased Hanasui lipstick at Arabelle TDM 2. Data were collected using a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²).The results indicate that price has a significant effect on purchasing decisions. Brand also has a considerable influence and is the most dominant variable affecting the decision to acquire HanaSu lipstick. Simultaneously, price and brand significantly influence purchasing decisions, with a coefficient of determination (R²) of 0,512. This means that 51.2% of the purchasing decision is influenced by price and brand, while the remaining 48.8% is influenced by other factors not examined in this study.It can be concluded that the combination of affordable pricing and strong brand image is the primary factor influencing consumers’ decisions to purchase Hanasui lipstick at Arabelle TDM 2 in Kupang City. These findings are expected to provide valuable input for the store and producers in improving their marketing strategies.Keywords: Price, Brand, Purchasing Decision, Hanasui, Cosmetics.